2021
DOI: 10.1101/2021.06.27.450077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota of ring-tailed lemurs (Lemur catta) vary across natural and captive populations and correlate with environmental microbiota

Abstract: Background: Inter-population variation in host-associated microbiota reflects differences in the hosts' environments, but this characterization is typically based on studies comparing few populations. The diversity of natural habitats and captivity conditions occupied by any given host species has not been captured in these comparisons. Moreover, intraspecific variation in gut microbiota, generally attributed to diet, may also stem from differential acquisition of environmental microbes - an understudied mecha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 134 publications
(130 reference statements)
3
2
0
Order By: Relevance
“…The distinct urban deer mice and similarity between captive populations lead to the result that environment type superseded any geographical effect on the gut microbiota. Geographical location has previously been shown to play a large role in shaping mammalian gut microbial composition [2,30], sometimes to the extent that it overcomes signals of environment type, as in a recent study of captive and wild lemurs [8]. The similarity of the two populations from undeveloped locations, located several states away, confirms the limited effect of geography in our study.…”
Section: Discussionsupporting
confidence: 87%
“…The distinct urban deer mice and similarity between captive populations lead to the result that environment type superseded any geographical effect on the gut microbiota. Geographical location has previously been shown to play a large role in shaping mammalian gut microbial composition [2,30], sometimes to the extent that it overcomes signals of environment type, as in a recent study of captive and wild lemurs [8]. The similarity of the two populations from undeveloped locations, located several states away, confirms the limited effect of geography in our study.…”
Section: Discussionsupporting
confidence: 87%
“…With growing recognition that animal hosts represent only one component of microbial landscapes, researchers are increasingly probing the relationships between host-associated and environmental microbiota. In a previous study on these same ring-tailed lemur populations, we showed that exposure to and acquisition of soil microbes likely contributed to interpopulation variation in gut microbiota (Bornbusch et al, 2021). Here, we expand on this finding, showing that the same pattern holds for ARGs: significant covariation between lemur gut and soil resistomes was found in two disturbed sites, ISA and BEZ.…”
Section: Discussionsupporting
confidence: 73%
“…Although not directly addressed in the present study, one such pressure may involve host sociality. Notably, the sitespecificity we observed in lemur resistomes mirrors the siteor group-specificity observed for microbiome composition in highly social species (Theis et al, 2012;Leclaire et al, 2014;Tung et al, 2015;Moeller et al, 2016), including the ring-tailed lemur (Bornbusch et al, 2021). The widely accepted mechanism underlying these patterns is the sharing of microbes between hosts, from many possible bodily sources, particularly between conspecific social partners (reviewed in Archie and Tung, 2015).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Temperate regions have been documented to have seasonal turnover of soil microbial populations, specifically in Colorado forests [ 22 ]. Bornbusch et al [ 23 ] also found that lemur GI microbiomes displayed seasonal fluctuations under human care. Seasonal changes in wild gorilla GI microbiome composition were previously documented by Gomez et al [ 10 ], although these changes were thought to be primarily driven by dietary changes rather than environmental changes.…”
Section: Introductionmentioning
confidence: 99%